The gods of Indian country: religion and the struggle for the American West - Graber, Jennifer (Oxford University Press, 2018)
"During the nineteenth century, white Americans sought the cultural transformation and physical displacement of Native people. Though this process was certainly a clash of rival economic systems and racial ideologies, it was also a profound spiritual struggle. The fight over Indian Country sparked religious crises among both Natives and Americans. In The Gods of Indian Country, Jennifer Graber tells the story of the Kiowa Indians during Anglo-Americans' hundred-year effort to seize their homeland. Like Native people across the American West, Kiowas had known struggle and dislocation before. But the forces bearing down on them-soldiers, missionaries, and government officials-were unrelenting. With pressure mounting, Kiowas adapted their ritual practices in the hope that they could use sacred power to save their lands and community. Against the Kiowas stood Protestant and Catholic leaders, missionaries, and reformers who hoped to remake Indian Country. These activists saw themselves as the Indians' friends, teachers, and protectors. They also asserted the primacy of white Christian civilization and the need to transform the spiritual and material lives of Native people. When Kiowas and other Native people resisted their designs, these Christians supported policies that broke treaties and appropriated Indian lands. They argued that the gifts bestowed by Christianity and civilization outweighed the pains that accompanied the denial of freedoms, the destruction of communities, and the theft of resources. In order to secure Indian Country and control indigenous populations, Christian activists sanctified the economic and racial hierarchies of their day. The Gods of Indian Country tells a complex, fascinating-and ultimately heartbreaking-tale of the struggle for the American West."--